Lead shot in Bewick's Swans - Evans, Mary E; Wood, N A; Kear, Janet (Wildfowl, 1973)
The totally protected Bewick's Swan Cygnus columbianus bewickii population was found by X-ray to have 34% of its individuals carrying shot in their tissues, a proportion not dissimilar to that in quarry species. A good deal of the shot appeared to have been received between the first and second winters. A higher level still was found in adults at least 5 years old. This may reflect changes in shooting regulations in part of the range. The effect of this illegal shooting is examined. The effectiveness of species by species legislation is questioned.